New campus-McLane Hall-0001
Science is stressed in the modern McLane Hall, Which provides 24 laboratories and 10 classrooms for biology and chemistry study. The elaborate science facility was constructed at the cost of aprproximately one and one-half million dollars. The building was named in honor of the late Charles L. Mclane, first president of Fresno State College.